Improving Students’ Vocabulary by Using Short Story - Bria, Gaudensiana Bete; Bouk, Edmundus; Seran, Yanuarius (Universitas Nurul Jadid, 2023)
The research was conducted due to students’ low ability in mastering English vocabulary. This research aimed at improving the second grade students’ vocabulary by using short story in SMP Satap Negeri Nian. This research used classroom action research. This research was carried out in one cycle with three actions given. This research was carried out by following CAR’s procedures consisting of planning, action or implementation, observation and reflection. Data were obtained through test results. The results of the preliminary study showed that students' vocabulary mastery were still very low with an average score of 48. Then, the researchers carried out cycle one, and the results of cycle one showed that students' vocabulary mastery had increased significantly, namely with an average score of 76. These results show that the use of short stories in teaching English can significantly increase the vocabulary mastery of second grade students at SMP Satap Negri Nian.